How Does Institutional Change Coincide with Changes in the Quality of Life? An Exemplary Case Study - Andreas Exenberger; Simon Hartmann (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
This paper provides a framework to assess correlations between the change of institutional functions (political centralization, plurality, rule of law, security of property, economic liberty, measured by 12 indicators) and improvements in human development (income, education, health) and violence limitations (conflict-related death tolls) to separate effective from ineffective institutional change. We apply this framework to a low-end institutional environment and provide a century case study of todays Democratic Republic of the Congo (DRC). Major results are threefold: first, we provide a thick description of institutional development in the Congo in a colonial and post-colonial and hence long-run setting; secondly, we identify periods of institutional change with distinctly different degrees of effectiveness; and thirdly, we are able to provide qualitative information on the questions of perspective (we follow a non-elitist approach), institutional connections, and timing of effects. Finally we propose extension of the framework, especially with respect to in-depth studies of critical transition periods, and its application to comparative case studies.
Keywords: O43; O55; O15; N37; N47; B52; 330; Institutions; Human Development; Congo (Democratic Republic); History; Effectiveness